2021
DOI: 10.1021/acs.jchemed.1c00808
|View full text |Cite
|
Sign up to set email alerts
|

Problem-Based Learning in an Introductory Inorganic Laboratory: Identifying Connections between Learner Motivation and Implementation

Abstract: Problem-based learning (PBL) is an acclaimed educational concept for laboratory teaching in chemistry, which significantly affects learner motivation. A central aim of PBL is to overcome educational problems with "cook-book" laboratories. For example, when students receive experimental instructions and apply the instructions similar to recipes, they do not necessarily understand what they do and why. However, research in problem-based laboratories still produces inconsistent and even contrasting results. A rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…The laboratory concept is derived from the industrial extraction of lithium from brine and is already published in the Journal of Chemical Education . The aim was to design contextual scientific and economic problems with topical relevance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The laboratory concept is derived from the industrial extraction of lithium from brine and is already published in the Journal of Chemical Education . The aim was to design contextual scientific and economic problems with topical relevance.…”
Section: Methodsmentioning
confidence: 99%
“…The laboratory concept is derived from the industrial extraction of lithium from brine and is already published in the Journal of Chemical Education. 33 The aim was to design contextual scientific and economic problems with topical relevance. The industrial extraction of lithium from brine is, despite its importance and timeliness for the world and economy, essentially based on a sequence of precipitation reactions.…”
Section: Lab Activity and Problem Designmentioning
confidence: 99%
“…Through questionnaires, student interviews, and teacher's observations in a logbook, Ferreira et al found evidence to support that the activities promoted intrinsic motivation. Wellho ¨fer and Lu ¨hken (2022) reported on a laboratory course designed around problem based learning. From student interviews, they found giving students the ability to autonomously propose experimental procedures was helpful in supporting student motivation.…”
Section: Self-determination Theorymentioning
confidence: 99%
“…Self-determination theory is a guiding framework for conceptualizing motivation in the context of chemistry education. ,,, Self-determination theory supposes that individuals are best when they are able to fulfill their psychological needs: competence (feeling skilled and capable), autonomy (being able to do something without a forced external reward), and relatedness (having someone else who supports you). Increased feelings of competence, autonomy, and relatedness are associated with increased intrinsic motivation. ,, In the context of completing organic chemistry courses, learners are best situated for success when they have useful feedback that can be used to measure their own level of understanding, when they feel that they are in control of their learning, and when they have meaningful and supportive relationships with their peers and educators in the course. ,, …”
Section: Introductionmentioning
confidence: 99%